Pengembangan Bahan Ajar Fiqih Model Majalah Anak Materi Thaharah Untuk Peningkatan Keefektifan Hasil Belajar - Benny Angga Permadi (Attadrib: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2021)
The aims of research and development included: 1) Design a magazine model development of teaching materials on the kid magazines model of thaharah material in class I Public Islamic Elementary School 2 Mojokerto. 2) Explain the feasibility of development of teaching materials on the kid magazines model of thaharah material as Instructional materials in class I Public Islamic Elementary School 2 Mojokerto. 3 ) Describe how much the increase of effectiveness of learning in teaching materials developed and applied magazine Instructional materials of Kid Magazines Model of Thaharah Material in class I Public Islamic Elementary School 2 Mojokerto. This type of research was research and development. The resulting product was Kid Magazines Model of Thaharah Material for students of class I Public Islamic Elementary School 2 Mojokerto. The model of development used the development model of Borg & Gall. The results of the development of teaching materials met valid criteria with the results of expert validation of material reached 90.91%, the validation results of design experts reached 89.28%, the results of teacher assessment reached 92.86%, small group trial reached 92.5%, and the test field experiment reached 90.83%. The average score of student learning outcomes of control class reached 87.22 and experimental class reached 78.51. On the results of the t-test using SPSS 16 with a significance level of 0.05 was obtained results tcount> ttable namely 3921> 2:00 meant that H0 was rejected and Ha. This showed that the teaching materials developed effective in improving the effectiveness of student learning outcomes in class I Public Islamic Elementary School 2 Mojokerto.